3D printing porous ceramic fiber modified plant insulating oil and preparation method and application thereof
Patent Information
- Application Number
- CN202610844426.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种3D打印多孔陶瓷纤维改性植物绝缘油及其制备方法和应用,解决现有纳米改性技术中存在的团聚、沉降、界面结合弱等问题
本发明公开了一种3D打印多孔陶瓷纤维改性植物绝缘油的制备方法,通过挤压式3D打印与淀粉微球造孔剂协同,在纤维内部及表面构筑了20-100 μm的微孔结构。烧结后微孔成为天然的电荷陷阱与电场均化单元,有效抑制局部放电通道发展。纤维的微米级宏观尺寸彻底克服了纳米颗粒因高表面能导致的团聚-沉降顽疾,从根源上实现了永久性分散稳定。
Smart Images

Figure CN122979022A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of plant-based insulating oil modification technology, specifically relating to a 3D-printed porous ceramic fiber modified plant-based insulating oil, its preparation method, and its application. Background Technology
[0002] Plant-based insulating oils, due to their outstanding advantages such as being environmentally friendly, biodegradable, and having a high flash point, have shown broad application prospects as a substitute for mineral insulating oils in power transformers. However, plant-based insulating oils also have inherent defects such as a high dielectric loss factor, poor thermal conductivity, and insufficient long-term thermal aging stability, which restrict their widespread application in high-voltage, large-capacity transformers.
[0003] To overcome the aforementioned bottlenecks, existing technologies generally employ nanoparticle modification. For example, patent document CN107123493A discloses a method for preparing plant-based insulating oil modified with silica nanoparticles, which exhibits good insulation and thermal conductivity. Hexamethyldisilazane-modified nano-silica is added to plant-based insulating oil at a mass ratio of 1 / 200, and the modified oil is obtained after mechanical stirring and ultrasonic dispersion, resulting in a certain improvement in breakdown voltage and thermal conductivity. However, the aforementioned nano-modification technology has significant limitations: First, due to their large specific surface area and high surface energy, nanoparticles are prone to agglomeration and sedimentation in the oil phase. Mechanical stirring, ultrasonic dispersion, or complex chemical modification can only temporarily maintain the dispersed state. Under long-term operation, thermal cycling, or electric field effects, the particles will re-agglomerate, leading to a decrease or even failure of the modification effect. Furthermore, the agglomerates may form conductive "bridges," thus degrading the insulation performance. Second, some solutions involve cumbersome processes (such as multi-step chemical reactions, requiring inert gas protection, and long-term high-temperature reactions), resulting in high costs and hindering industrial-scale promotion. Furthermore, existing nano-modification technologies mainly rely on the interfacial effect or charge trapping effect of nanoparticles, with a single mechanism of action and limited effect on delaying the long-term thermal aging process of insulating oil. Summary of the Invention
[0004] The purpose of this invention is to provide a 3D-printed porous ceramic fiber modified plant insulating oil, its preparation method and application, to solve the problems of agglomeration, sedimentation and weak interfacial bonding in existing nano-modification technologies.
[0005] This invention is achieved through the following technical solution: This invention discloses a method for preparing 3D-printed porous ceramic fiber modified plant insulating oil, comprising the following steps: (1) Printing ink is prepared with alumina powder, pore-forming agent and solvent as the main components, and a porous ceramic fiber preform with an interlaced mesh structure is formed by extrusion 3D printing; (2) The porous ceramic fiber preform is sintered at high temperature under a protective atmosphere, and then the sintered fiber is immersed in a silane coupling agent solution for surface modification treatment. After being taken out and dried, the modified ceramic fiber is obtained. (3) Modified ceramic fibers are added to plant insulating oil, and after ultrasonic dispersion, antioxidants are added and then vacuum degassing is performed to obtain 3D printed porous ceramic fiber modified plant insulating oil.
[0006] Further, in step (1), the composition of the printing ink by volume percentage is: 30-40 vol% alumina powder, 3-8 vol% pore-forming agent, 50-65 vol% solvent, and pH adjuster is added to adjust the pH to 4-5.
[0007] Furthermore, the pore-forming agent is starch microspheres, the solvent is deionized water, and the pH adjuster is citric acid.
[0008] Furthermore, in step (1), the printing pressure of the extrusion 3D printing is 0.2-0.5 MPa, and the nozzle temperature is 20-30 ℃.
[0009] Furthermore, the porosity of the porous ceramic fiber preform with the interlaced mesh structure is greater than 50%, and the pore size ranges from 20 to 100 μm.
[0010] Furthermore, in step (2), the high-temperature sintering temperature is 900-1200 ℃, the time is 2-4 hours, and the protective atmosphere is nitrogen or argon.
[0011] Furthermore, in step (2), the silane coupling agent is KH-550, with a solution concentration of 1-5 wt%, an impregnation time of 20-40 minutes, and a drying temperature of 70-90 ℃.
[0012] Furthermore, in step (3), the vegetable insulating oil is a refined vegetable oil with an acid value of less than 0.1 mg KOH / g; The amount of modified ceramic fiber added is 5-10 wt% of the weight of the vegetable insulating oil. The ultrasonic dispersion power is 150-250 W, and the time is 20-40 minutes; The antioxidant is BHT, and the amount of antioxidant added is 0.02-0.1 wt% of the weight of the vegetable insulating oil. The vacuum degassing process is carried out at a temperature of 50-70℃ for 0.5-2 hours.
[0013] The present invention also discloses the 3D-printed porous ceramic fiber modified plant insulating oil prepared by the aforementioned preparation method.
[0014] The present invention also discloses the application of the 3D printed porous ceramic fiber modified plant insulating oil in transformers or power equipment.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing 3D-printed porous ceramic fibers modified with plant-based insulating oil. Through extrusion 3D printing in synergy with a starch microsphere pore-forming agent, a microporous structure of 20-100 μm is constructed inside and on the surface of the fibers. After sintering, the micropores become natural charge traps and electric field homogenization units, effectively suppressing the development of partial discharge channels. The micron-scale macroscopic size of the fibers completely overcomes the agglomeration and sedimentation problems caused by the high surface energy of nanoparticles, achieving permanent dispersion and stability from the root cause.
[0016] Surface modification of sintered fibers using silane coupling agents involves the hydrolytic condensation of the alkoxy groups of the coupling agent with the hydroxyl groups on the ceramic fiber surface to form Si-O-Al covalent bonds, while the amino groups at the amino terminus interact with fatty acid groups in vegetable oil through hydrogen bonding or van der Waals forces. This chemical bridging mechanism significantly reduces the oil-solid interfacial tension, transforming the fiber from hydrophilic to oleophilic. This not only achieves long-term ultrasonic-static settling-free operation but also effectively inhibits the accumulation of oleic acid decomposition byproducts at the interface under high-temperature aging, thus slowing down the overall aging process of the insulating oil.
[0017] Porous fibers interlock in the oil phase to form a three-dimensional thermally conductive / uniform field network, fundamentally solving the problem of filler agglomeration and sedimentation in existing nano-modification technologies. Regarding process costs, the alumina, starch, and water used in this method are all readily available raw materials, and the 3D printing, tube furnace, and ultrasonic equipment are mature and the steps are simple, significantly reducing costs. In terms of environmental friendliness, starch is a bio-based pore-forming agent that completely decomposes during sintering.
[0018] Furthermore, the sintering temperature is 900-1200 ℃. This temperature range allows for sufficient sintering of alumina ceramics (the sintering temperature of alumina is usually above 1400 ℃, but can be reduced to 900-1200 ℃ by adding starch pore-forming agents and fine powders) while preventing pore collapse. A protective atmosphere (nitrogen or argon) prevents excessively rapid starch combustion, which could lead to uneven pore size, ensuring the controllability of the porous structure. This enables the production of structurally stable porous ceramic fibers with lower energy consumption, reducing process costs and energy consumption.
[0019] This invention also discloses a 3D-printed porous ceramic fiber modified plant insulating oil prepared by the above method. This modified plant insulating oil has unique microstructural features: it contains 3D-printed custom-made porous ceramic fibers, which overlap to form a three-dimensional network. The fibers contain micropores of 20-100 μm inside and on the surface. This structure distinguishes the product from existing nanoparticle modified oils (which are spherical particles dispersed in the oil in an isolated manner) and ordinary fiber modified oils (which have no porous structure and no network overlap). The solid fiber modified oil in Comparative Example 4, due to the lack of a porous structure, only showed an 18.3% increase in dielectric strength; while the products in Examples 1-5 all achieved a dielectric strength increase of ≥35%, an aging degradation rate of ≤5%, and an initial decomposition temperature of ≥295 ℃. Attached Figure Description
[0020] Figure 1 This is a flowchart of a method for preparing 3D-printed porous ceramic fiber modified plant insulating oil according to the present invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the present invention clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention; that is, the described embodiments are only a part of the embodiments of the present invention, and not all of them.
[0022] The detailed description of the embodiments of the present invention provided in the following drawings is not intended to limit the scope of the claimed invention, but merely to illustrate one selected embodiment of the invention. All other embodiments obtained by those skilled in the art based on the drawings and embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0023] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0024] Example 1 Raw materials and equipment: refined rapeseed oil (acid value 0.08 mg KOH / g), alumina powder (purity 99.9%), starch microspheres (particle size 50 μm). Required equipment includes an extrusion 3D printer, a tube furnace, and an ultrasonic cleaner.
[0025] like Figure 1 As shown, the preparation process is as follows: (1) Preparation of porous ceramic fiber preform: Alumina powder (35%), starch microspheres (5%) and deionized water (60%) were mixed by volume ratio, and citric acid was added to adjust the pH to 4.5. The mixture was stirred for 1 hour to form a uniform ink.
[0026] 3D printing: A 10 cm × 10 cm × 1 mm interlaced mesh fiber preform was printed at a printing pressure of 0.3 MPa and room temperature.
[0027] (2) Heat treatment and surface modification: The preform was sintered at 1150 °C for 3 hours in a nitrogen atmosphere. After cooling, it was immersed in a 2 wt% KH-550 ethanol solution for surface modification for 30 minutes, and then dried at 80 °C.
[0028] (3) Plant insulating oil composite modification: Take 100 g rapeseed oil, add 8 wt% of the above modified fiber, and after ultrasonic treatment at 200 W power for 30 minutes, add 0.05 wt% BHT antioxidant, and finally degas under vacuum at 60 ℃ for 1 hour.
[0029] Performance Verification: The prepared modified insulating oil achieved a dielectric strength of 42 kV / mm, while the base oil was 30 kV / mm. After 500 hours of accelerated aging at 130℃, its dielectric strength remained above 40 kV / mm. Thermogravimetric analysis showed that the initial decomposition temperature of the modified insulating oil was 302℃. The thermal conductivity remained stable at 0.15 W / m·K. Electric field simulation analysis confirmed that the porous structure of the fibers effectively homogenized the electric field distribution, preventing the occurrence of breakdown hotspots.
[0030] Example 2 Raw materials and equipment: Same as Example 1, but with different proportions and process parameters.
[0031] Preparation process: (1) Preparation of porous ceramic fiber preform: Alumina powder (30%), starch microspheres (8%), and deionized water (62%) were mixed by volume ratio, and citric acid was added to adjust the pH to 4.0. The mixture was stirred for 1 hour to form a uniform ink. Under the conditions of printing pressure of 0.2 MPa and nozzle temperature of 20 ℃, an interlaced mesh fiber preform was printed with a designed porosity of 70% and a pore size of about 80 μm.
[0032] (2) Heat treatment and surface modification: The preform was heated to 900 °C at 5 °C / min under an argon atmosphere and sintered at that temperature for 4 hours. After cooling, it was immersed in 1 wt% KH-550 ethanol solution for 40 minutes and dried at 70 °C.
[0033] (3) Plant insulating oil composite modification: Take 100 g of refined rapeseed oil, add 5 g (5 wt%) of modified ceramic fiber, ultrasonically disperse at 150 W for 40 minutes, add 0.02 g (0.02 wt%) of BHT, and degas at 50 ℃ under vacuum for 2 hours.
[0034] Performance testing: The modified oil has a dielectric strength of 40.5 kV / mm, which is 35% higher than that of the base oil (30 kV / mm); thermal conductivity is 0.145 W / m·K; after 500 hours of accelerated aging at 130℃, the dielectric strength decay rate is 4.2%; thermogravimetric analysis shows that the initial decomposition temperature is 298℃.
[0035] Example 3 Raw materials and equipment: Same as Example 1.
[0036] Preparation process: (1) Preparation of porous ceramic fiber preform: Alumina powder (40%), starch microspheres (3%), and deionized water (57%) were mixed by volume ratio, and citric acid was added to adjust the pH to 5.0. The mixture was stirred for 1 hour. Printing was carried out under the conditions of printing pressure of 0.5 MPa and nozzle temperature of 30 ℃. The designed porosity was 55% and the pore size was about 25 μm.
[0037] (2) Heat treatment and surface modification: The temperature was increased to 1200 °C at 5 °C / min under a nitrogen atmosphere and sintered for 2 hours. After cooling, it was immersed in 5 wt% KH-550 ethanol solution for 20 minutes and dried at 90 °C.
[0038] (3) Plant insulating oil composite modification: Take 100 g rapeseed oil, add 10 g (10 wt%) modified fiber, ultrasonically disperse at 250 W for 20 minutes, add 0.1 g (0.1 wt%) BHT, and degas at 70 ℃ under vacuum for 0.5 hours.
[0039] Performance testing: The modified oil has a dielectric strength of 43.5 kV / mm, which is 45% higher than that of the base oil; a thermal conductivity of 0.158 W / m·K; after 500 hours of accelerated aging at 130℃, the dielectric strength decay rate is 2.9%; thermogravimetric analysis shows that the initial decomposition temperature is 305℃.
[0040] Example 4 Raw materials and equipment: Same as Example 1, but the pore-forming agent uses starch microspheres of different particle sizes (average particle size 30 μm) to obtain smaller pore sizes.
[0041] Preparation process: (1) Preparation of porous ceramic fiber preform: Alumina powder (38%), starch microspheres (6%), and deionized water (56%) were mixed by volume and the pH was adjusted to 4.5. Printing was carried out at a printing pressure of 0.35 MPa and room temperature, with a designed porosity of 65% and a pore size of about 20 μm.
[0042] (2) Heat treatment and surface modification: The temperature was increased to 1050 °C at 5 °C / min under a nitrogen atmosphere and sintered at that temperature for 3.5 hours. After cooling, it was immersed in 3 wt% KH-550 ethanol solution for 30 minutes and dried at 80 °C.
[0043] (3) Plant insulating oil composite modification: Take 100 g rapeseed oil, add 7 g (7 wt%) modified fiber, ultrasonically disperse at 180 W for 35 minutes, add 0.06 g BHT, and degas under vacuum at 60 ℃ for 1.5 hours.
[0044] Performance testing: The modified oil has a dielectric strength of 41.8 kV / mm, which is 39.3% higher than that of the base oil; a thermal conductivity of 0.152 W / m·K; and a decay rate of 3.8% after 500 hours of accelerated aging at 130℃. Thermogravimetric analysis shows that the initial decomposition temperature is 300℃.
[0045] Example 5 Raw materials and equipment: Same as Example 1, but refined soybean oil (acid value 0.07 mg KOH / g) was used as the vegetable insulating oil to verify the adaptability of different vegetable oil matrices.
[0046] Preparation process: (1) Preparation of porous ceramic fiber preform: Alumina powder (35%), starch microspheres (5%) and deionized water (60%) were mixed by volume ratio, pH 4.5, printing pressure 0.3 MPa, and printed at room temperature. The porosity was about 60% and the pore size was 50 μm.
[0047] (2) Heat treatment and surface modification: sintering at 1150 ℃ for 3 hours, modification with 2 wt% KH-550 for 30 minutes, and drying at 80 ℃.
[0048] (3) Plant insulating oil composite modification: Take 100 g refined soybean oil, add 8 g modified fiber, sonicate at 200 W for 30 minutes, add 0.05 g BHT, and degas at 60 ℃ for 1 hour.
[0049] Performance testing: The dielectric strength of the base soybean oil was 28 kV / mm, which was increased to 39.5 kV / mm after modification, an increase of 41%; the thermal conductivity was 0.148 W / m·K; the decay rate after aging was 4.0%; thermogravimetric analysis showed that the initial decomposition temperature was 295 ℃ (275 ℃ for the base oil).
[0050] The following is the control group experiment: Comparative Example 1 (Fiber addition too low) The only difference between Comparative Example 1 and Example 1 is that the amount of modified ceramic fiber added is 3 wt% (instead of 8 wt%). All other preparation conditions are exactly the same.
[0051] Test results: The dielectric strength was only 33.2 kV / mm, significantly lower than that of Example 1 (40%). This indicates that when the fiber content is less than 5 wt%, it is difficult to form an effective three-dimensional network in the oil, and the modification effect is not significant.
[0052] Comparative Example 2 (Excessive Fiber Addition) The only difference between this comparative example and Example 1 is that the amount of modified ceramic fiber added is 15 wt%. All other preparation conditions are exactly the same. During the preparation process, it was found that the viscosity of the oil sample increased significantly and its fluidity decreased after ultrasonic dispersion; significant sedimentation occurred after standing for 24 hours.
[0053] Test results: The initial dielectric strength was 44.1 kV / mm (an increase of 47%), but it dropped to 34.2 kV / mm after aging (a decrease of 22.5%), and the dielectric strength of the upper oil sample was only 31.5 kV / mm after 30 days of standing. This indicates that when the addition amount exceeds 10 wt%, the dispersion stability deteriorates and the long-term performance is severely degraded.
[0054] Comparative Example 3 (without surface modification by coupling agent) The only difference between this comparative example and Example 1 is that the sintered fibers in step (2) are not subjected to KH-550 surface modification treatment and are directly added to the vegetable insulating oil. All other preparation conditions are exactly the same.
[0055] Test results: The initial dielectric strength was 36.8 kV / mm (an increase of 22.7%), lower than that of Example 1; fiber sedimentation occurred after 7 days of standing, and the dielectric strength of the upper oil sample decreased to 32.1 kV / mm after 30 days, with a sedimentation rate of 65%. This indicates that surface modification is crucial for fiber dispersion stability and interfacial bonding.
[0056] Comparative Example 4 (Solid ceramic fibers without porous structure) The difference between this comparative example and Example 1 is that starch microspheres (i.e., 40 vol% alumina powder and 60 vol% deionized water) are not added to the printing ink in step (1), and solid ceramic fibers are obtained after sintering, while the other conditions are the same. Test results: The initial dielectric strength is 35.5 kV / mm (an increase of 18.3%), and the decay rate is 9.2% after 500 hours of accelerated aging at 130℃. Its insulation improvement and long-term stability are both inferior to Example 1 (40% improvement, 3.6% decay), proving the contribution of the porous structure to the electric field homogenization and long-term stability.
[0057] Comparative Example 5 (Blank Control Group) Refined rapeseed oil (acid value 0.08 mg KOH / g) from the same batch as in Example 1 was used as the performance benchmark. No modifiers were added, and the oil was treated under the vacuum degassing conditions of Example 1. The test results were: dielectric strength 30 kV / mm, thermal conductivity 0.12 W / m·K, and initial decomposition temperature 280 ℃.
[0058] As can be seen from the above Examples 1-5 and Comparative Examples 1-5: In Example 1, the surface-modified porous ceramic fibers showed no sedimentation after 30 days of standing, while the unmodified fibers in Comparative Example 3 showed significant sedimentation within 7 days. After 500 hours of accelerated aging at 130°C, the dielectric strength attenuation rate of Example 1 was only 3.6%, while the attenuation rate of Comparative Example 2 (excessive addition) was as high as 22.5%, and the attenuation rate of Comparative Example 4 (solid fiber) was 9.2%. This demonstrates that the modified oil within the preferred parameter range of this invention (5-10 wt% addition, porous structure, coupling agent modification) has excellent long-term dispersion stability and anti-aging properties. Regarding insulation performance, the dielectric strength of Example 1 increased from 30 kV / mm to 42 kV / mm (a 40% increase), while Comparative Example 4, using solid fibers, only saw an 18.3% increase, demonstrating the electric field homogenization effect of the porous structure. Comparative Example 1, with its low fiber addition, only saw a 10.7% increase, and Comparative Example 3, without coupling agent modification, only saw a 22.7% increase, both significantly lower than Example 1. This indicates that the synergistic effect of fiber addition, porous structure, and surface modification is key to achieving high insulation strength. Regarding thermal stability, the initial decomposition temperature of Example 1 increased from 280℃ to 302℃, and that of Example 3 to 305℃, while the blank control of Comparative Example 5 remained at 280℃, demonstrating that the introduction of porous ceramic fibers effectively increased the thermal decomposition temperature of the insulating oil. Regarding interfacial bonding, Comparative Example 3, without coupling agent treatment, experienced a significant increase in sedimentation rate and performance degradation, demonstrating that coupling agent modification effectively solved the problem of a weak fiber-oil interface.
[0059] This invention reduces energy consumption through bio-based pore-forming agents and low-temperature sintering; improves fiber-oil interface compatibility through coupling agent modification; and ensures safe operation throughout the entire process (it can be implemented using conventional laboratory equipment). It significantly overcomes the shortcomings of existing methods. The modified vegetable insulating oil exhibits a dielectric strength increase of ≥40% compared to the base oil. The porous fiber network effectively homogenizes the electric field and suppresses partial discharge. After accelerated aging testing, its insulation strength degradation rate is less than 5%, significantly superior to traditional mineral oils.
[0060] The initial decomposition temperature of the modified oil is increased to about 300 ℃; the introduction of ceramic fibers improves thermal conductivity and reduces operating temperature rise; the surface modification layer effectively reduces the generation of oleic acid decomposition byproducts and improves interface stability.
[0061] The preparation process uses a bio-based pore-forming agent, and the utilization rate of bio-based materials throughout the process is greater than 90%, thus reducing the carbon footprint. The process is simple, requires no complex equipment, and has good prospects for industrialization.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing 3D-printed porous ceramic fiber modified plant insulating oil, characterized in that, Includes the following steps: (1) Printing ink is prepared with alumina powder, pore-forming agent and solvent as the main components, and a porous ceramic fiber preform with an interlaced mesh structure is formed by extrusion 3D printing; (2) The porous ceramic fiber preform is sintered at high temperature under a protective atmosphere, and then the sintered fiber is immersed in a silane coupling agent solution for surface modification treatment. After being taken out and dried, the modified ceramic fiber is obtained. (3) Modified ceramic fibers are added to plant insulating oil, and after ultrasonic dispersion, antioxidants are added and then vacuum degassing is performed to obtain 3D printed porous ceramic fiber modified plant insulating oil.
2. The preparation method according to claim 1, characterized in that, In step (1), the composition of the printing ink by volume percentage is: 30-40 vol% alumina powder, 3-8 vol% pore-forming agent, 50-65 vol% solvent, and pH adjuster is added to adjust the pH to 4-5.
3. The preparation method according to claim 2, characterized in that, The pore-forming agent is starch microspheres, the solvent is deionized water, and the pH adjuster is citric acid.
4. The preparation method according to claim 1, characterized in that, In step (1), the printing pressure of the extrusion 3D printing is 0.2-0.5 MPa and the nozzle temperature is 20-30 ℃.
5. The preparation method according to claim 1, characterized in that, The porous ceramic fiber preform with the interlaced mesh structure has a porosity greater than 50% and a pore size range of 20-100 μm.
6. The preparation method according to claim 1, characterized in that, In step (2), the high-temperature sintering temperature is 900-1200 ℃, the time is 2-4 hours, and the protective atmosphere is nitrogen or argon.
7. The preparation method according to claim 1, characterized in that, In step (2), the silane coupling agent is KH-550, the solution concentration is 1-5 wt%, the impregnation time is 20-40 minutes, and the drying temperature is 70-90 ℃.
8. The preparation method according to claim 1, characterized in that, In step (3), the vegetable insulating oil is a refined vegetable oil with an acid value of less than 0.1 mg KOH / g; The amount of modified ceramic fiber added is 5-10 wt% of the weight of the vegetable insulating oil. The ultrasonic dispersion power is 150-250 W, and the time is 20-40 minutes; The antioxidant is BHT, and the amount of antioxidant added is 0.02-0.1 wt% of the weight of the vegetable insulating oil. The vacuum degassing process is carried out at a temperature of 50-70℃ for 0.5-2 hours.
9. The 3D-printed porous ceramic fiber modified plant insulating oil prepared by the preparation method according to any one of claims 1-8.
10. The application of the 3D-printed porous ceramic fiber modified vegetable insulating oil according to claim 9 in transformers or power equipment.
Citation Information
Patent Citations
SiO2 nano-particle modified vegetable insulating oil having good insulation and thermal conductivity and preparation method thereof
CN107123493A